Paediatric Colonoscopy: Experience from Pediatric Gastroenterology and Nutrition Department, BSMMU (Bangladesh Journal of Child Health, 2021)
Background: Colonoscopy of the lower gastrointestinal tract has both diagnostic and therapeutic value.Objective: This cross-sectional study aimed to investigate the indications, findings and complications of children who underwent the colonoscopy.Materials & Methods: We studied the children between 1 and 18 years of age who presented with various indications and underwent both diagnostic and therapeutic colonoscopy in the Department of PGN, BSMMU, Dhaka from January 2015 to February 2018.Results: Among the total 332 patients reviewed,61.7% (205) were male and 38.3% (127)with a male to female ratio of 1.61:1. The most common (69.8%) indication was lower gastrointestinal bleeding (LGIB) followed by diarrhea (15.9%) and altered bowel (14%) as well. No serious complications occurred during the procedures. A total of 211 patients (63.5%) received a diagnosis, including 137 (41.3%) patients with colorectal polyps, erythema 40(12%) and diffuse nonspecific colitis 34(10.2%).Ninety four percent polyps are located in recto-sigmoid region. Juvenile polyp was the most common pathological findings.Conclusion: LGIB is the commonest indication for pediatric colonoscopy. Pediatric colonoscopy is effective diagnostic as well as therapeutic option for lower GI pathology.BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 25-28